The management of mass concrete pours to thick raft foundations in Singapore - Goh, Wee Hong. (2009)
This dissertation attempts to give an insight into the management aspects of carrying out large volume mass concrete pours locally. The topics covered were meant to show the multitudinous considerations that went into managing eight such contemporary exercises carried out on a thick raft foundation in Singapore.